Analysis of Total Phenol and Flavonoid Compounds in Temulawak (Curcuma xanthorrhiza Roxb.) Tablets Based on Differences in Maltodextine Concentration - Indriani, Dina Wahyu; Mutiarani, Nadya; Lastriyanto, Anang (Fakultas Teknologi Industri Pertanian, 2023)
Temulawak (Curcuma xanthorrhiza Roxb.) has empirical phenolics and flavonoids which can act as antioxidants. The purpose of this study was to produce tablets of temulawak (Curcuma xanthorrhiza Roxb.) with variations in the addition of maltodextrin concentration and to find the best results. This research was conducted using a non-factorial Randomised Block Design (RBD) with 3 treatment levels, the ratio of maltodextrin to 1:2 (50%), 1:4 (25%) and 1:6 (16.70%). The results of this study showed that all tablets formed met the requirements of BPOM Number 32 of 2019 such that the tablets must be less than or equal to 10% and all the shaped tablets had a uniform weight. The tablets with 1:2 (50%) treatment had the highest value which was able to produce the highest total mean value of phenolics and flavonoids when compared with 1:4 (25%), 1:6 (16,70%) and control treatments. In a 1:2 (50%) treatment, the total phenolic value was 3.63 mg GAE/g ± 0.09, while the total flavonoid value was 6.11 mg QE/g ± 0.30. Therefore, it can be stated that the maltodextrin concentration treatment with a ratio of 1:2 (50%) was the optimum method for producing temulawak (Curcuma xanthorrhiza Roxb.) tablets in this study.